THE EFFECTIVENESS OF THE APPLICATION OF THE TYPE COOPERATIVE LEARNING MODEL MAKE A MATCH AGAINST STUDENT LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN CLASS X SMA 3 SINJAI (International Conference on Social and Islamic Studies, 2022)
This thesis discusses the effect of the make a match cooperative learning model on student learning outcomes in class X Islamic Religious Education at SMA Negeri 3 Sinjai. This study aims to: (1) determine the learning outcomes of Islamic Religious Education students who are taught without using the make a match type cooperative learning model in class X at SMA Negeri 3 Sinjai, (2) determine the learning outcomes of Islamic Religious Education students who are taught with using the make a match type of cooperative learning model in class X at SMA Negeri 3 Sinjai, (3) analyzing the application of the make a match type cooperative learning model has an effect on the learning outcomes of students in Islamic Religious Education in class X at SMA Negeri 3 Sinjai. This research is a quantitative research with a quasi-experimental research design with a non-equivalent control group design. The instruments used in this study were observation sheets and tests. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. Descriptive research results obtained an average learning outcomes Islamic Religious Education students in class X IPS 2 who are taught without using the make a match type cooperative learning model are 62.67, and are in the "high" category while the average learning outcomes of students in class X IPS 1 who are taught using  the cooperative learning model of the make a match type is 74.33 and is in the "high" category. Based on the results of inferential statistical analysis using hypothesis testing (paried samples test) SPSS version 20 data processing obtained Sig = 0.000, it can be concluded that Ho is rejected and Ha is accepted because sig (2-tailed) < a or (0.000 0.05), thus the final conclusion of the study or the hypothesis received by Ha is that there is influence due to differences in student learning outcomes in Islamic Religious Education subjects between classes taught without using a model make a match cooperative learning with classes taught using make a match cooperative learning models. The implication of this research is that researchers hope that the make a match type cooperative learning model can be considered as an alternative in the teaching and learning process and the results of this study can be used as material for consideration to improve the quality education, especially regarding learning models in senior high schools, especially in SMA Negeri 3 Sinjai.